Russia-Ukraine War: An Opportunity to Indian Agricultural Sector (International Journal of Food and Nutritional Sciences, 2022)
This research paper has enlightened on opportunity to Indian agro products in world market in warlike condition between Russia and Ukraine. Ongoing Russia Ukraine war, world agriculture productssupply chain has been disrupting. Many agricultural products prices are increasing. But this war hasopened golden opportunity for Indian Agro products such as Cereals, Dairy produce, fruits, Vegetables, Oilseeds and oleaginous fruits etc. Hence, this war situation India can export all these agro products which arecomparatively advantages (RCA >1) in world market.